2020
DOI: 10.5812/ircmj.98803
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Cytotoxic Effect of Silver Nanoparticles on Human Lymphocytes and HPB-ALL Cell Line: As an In Vitro Study

Abstract: Background: Cancer is currently the second leading cause of death worldwide that is originated from cell growth and proliferation without control. Acute lymphoblastic leukemia (ALL) is one of the types of leukemia that affects lymphocyte maturation and it is common among children. Silver nanoparticles are considered one of the targeted chemotherapy methods by creating cytotoxicity. Objectives: In this research, a comparative study of cytotoxic effect of silver nanoparticles was evaluated on human lymphocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“… 64 , 65 The amount of apoptosis in the T group was approximately 1.5 times of rats treated with AgNPs (TAg) (43.5 ± 0.46). Farahani et al 66 stated the ability of AgNPs to induce apoptosis in cancerous cell lines with low toxicity on normal liver cells and the lymphocytes. Mahjoub et al 67 showed that AgNPs administration did not cause changes in the WBC formula, but it can induce which activation in murine lymphocytes after a few hours of exposure to AgNPs.…”
Section: Discussionmentioning
confidence: 99%
“… 64 , 65 The amount of apoptosis in the T group was approximately 1.5 times of rats treated with AgNPs (TAg) (43.5 ± 0.46). Farahani et al 66 stated the ability of AgNPs to induce apoptosis in cancerous cell lines with low toxicity on normal liver cells and the lymphocytes. Mahjoub et al 67 showed that AgNPs administration did not cause changes in the WBC formula, but it can induce which activation in murine lymphocytes after a few hours of exposure to AgNPs.…”
Section: Discussionmentioning
confidence: 99%